Dynamical Behavior of a Rumor Transmission Model with Psychological Effect in Emergency Event - Liang'an Huo; Tingting Lin; Peiqing Huang (Abstract and Applied Analysis)
A rumor transmission model with nonmonotonic incidence rate was proposed, which provides excellent explanations of the “psychological” effect with rumor spreading in emergency event. By carrying out a global analysis of the model and studying the stability of the rumor-free equilibrium and the rumor-endemic equilibrium, we showed that either the number of infective individuals tends to zero as time evolves or the rumor persists. Finally, recommendations for policy makers and consulting advice for related commissions are explored in the case study of crazy rumors propagated for the iodized sail shortage panic in China.